Homocide co-victims: confidence in the criminal justice system. Issue 3 (19th September 2019) - Brown, Elaine; Crego, Jonathan
Abstract : Purpose: The purpose of this paper is to address the phenomenology of family members of homicide victims; known as "co-victims". In particular, co-victims experiences of the criminal justice system (CJS) in England and Wales. Design/methodology/approach: In 2018, 10 kV methodology facilitated an electronic-focus group. Anonymously, volunteers from families of homicide victims responded to key questions in a session entitled "a conversation which matters: confidence". The thematic analysis presents the responses to three questions around "what works" and "what does not" in CJS practice. Findings: The responses indicate four themes in relation to confidence building: communication and information; outcome; honesty and fairness; and family support. Responses indicate three themes in relation to what the CJS does well: family liaison officers, homicide detectives and court services. Responses indicate three themes in relation to what is not working: court proceedings, police budget cuts and preventative interventions. Research limitations/implications: The research considers benefits and limitations of methodology and makes suggestions for how these facets could be addressed by future research. Practical implications: The research findings reveal good practice and points for attention to support confidence building in the CJS. Amongst other considerations, the work advances CJS practical good practice principles from the perspective of co-victims: education, interpersonal relations, working together, communication and justice. Originality/value: Findings are of value to CJS policy makers, training and education for co-victim support, police and academics.